Enhancing Seed Germination and Seedlings Growth of Khao Dawk Mali 105 Rice Cultivar via Seed Coating and Infrared Drying Apparatus - Laohavanich, Juckamas; Phola, Waranya; Phuhongphet, Umaporm; Sinsiri, Wantana; Sudwilai, Wilailux; Hu, Wei; Senakun, Chadaporn (Trends in Sciences, 2024)
Seed coating techniques had emerged as a promising approach for precise planting and safeguarding crops against environmental stresses. Simultaneously, infrared drying, renowned for its cost-effectiveness and efficiency, held promises for enhancing the quality of drying processes. This investigation delved into the procedures applied to Khao Dawk Mali 105 rice seeds during the coating and drying process using a prototype of the hexagonal drum. The results found that the drying temperature (factor B) and duration of drying time (factor C) had substantial primary effects (p ≤ 0.05), while the drum rotational speed (factor A) did not exert a noteworthy influence. Additionally, meaningful interactions were observed among the factors AB, AC, BC, and ABC. Impressively, it resulted in germination rates of 80.56 and 80.25 %, coupled with germination indices of 84.88 and 85.47 %, when utilizing a drum speed of 20 rpm, a drying temperature of 45 °C, and a drying time of 8 min (R-204508), and a drum speed of 10 rpm, a drying temperature of 45 °C, and a drying time of 8 min (R-104508), respectively. Additionally, the mean germination time amounted to 9.64 days, and the length of the rice seedling stem reached 13.66 cm when employing a drum speed of 20 rpm, a drying temperature of 50 °C, and a drying time of 8 min (R-205008). These discoveries emphasized the potential of the prototype's seed coating and infrared drying technology integration to improve rice germination and subsequent growth. This enhancement could ultimately result in higher yields and increased productivity, especially in small-scale agricultural settings. HIGHLIGHTS These discoveries emphasized the potential of the prototype's seed coating and infrared drying technology integration to improve rice germination and subsequent growth. This enhancement could ultimately result in higher yields and increased productivity, especially in small-scale agricultural settings. Ensuring precise control over drying temperature and duration is of paramount importance in establishing optimal and consistent conditions for the germination and subsequent growth of rice seeds, thereby augmenting plant vigor and overall yield The investigation determined optimal coating and drying conditions, encompassing a drum speed of 20 rpm, a drying temperature of 45 °C, and a drying duration of 8 min (treatment R-204508), along with a drum speed of 20 rpm, a drying temperature of 45 °C, and a drying time of 8 min (treatment R-104508). These conditions resulted in the highest mean germination rates and germination indices. GRAPHICAL ABSTRACT